2002
DOI: 10.1046/j.1440-6047.11.s.7.6.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E on plasma malondialdehyde, antioxidant enzyme levels and the rates of wound closures during wound healing in normal and diabetic rats

Abstract: Vitamin E is composed of various subfamilies that include tocopherols and tocotrienols. These compounds have antioxidant properties but differ in structure, dietary source and potency. In this study we evaluated the efficacy of alpha-tocopherol as an antioxidant and its role in wound closure in normal and streptozotocin-induced diabetic rats. The healing of 6 cm linear incisions created on the back of each male Sprague-Dawley rat (250-300 g) was monitored by measuring the length of the wounds daily. The rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 13 publications
4
44
2
3
Order By: Relevance
“…In the present study vitamin E attenuated the increase in lipid hydroperoxide, accompanied by a concomitant increase in the activities of GSH-Px and SOD, which modulated the concentration of ROS. These data were consistent with studies reporting that vitamin E exerted a beneficial effect on the antioxidant enzyme activity in type 1 diabetes (Varvarovská et al 2004;Musalmah et al 2002). Indeed, antioxidant therapy could prevent a disturbance in the mechanism of protection against the deleterious cellular and biomolecular effects that led to alterations in the cell function.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study vitamin E attenuated the increase in lipid hydroperoxide, accompanied by a concomitant increase in the activities of GSH-Px and SOD, which modulated the concentration of ROS. These data were consistent with studies reporting that vitamin E exerted a beneficial effect on the antioxidant enzyme activity in type 1 diabetes (Varvarovská et al 2004;Musalmah et al 2002). Indeed, antioxidant therapy could prevent a disturbance in the mechanism of protection against the deleterious cellular and biomolecular effects that led to alterations in the cell function.…”
Section: Discussionsupporting
confidence: 91%
“…Of particular interest is the increased SOD level observed in ducklings from the maternal high-vitamin premix group. The effects of dietary vitamins on antioxidant enzyme activities remain controversial (Musalmah et al, 2002;Beytut and Aksakal, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…And thus oxidative stress induces cellular dysfunction and retards angiogenesis and the healing process [21]. Many studies [13,14,[22][23][24] have concluded that the antioxidants help to maintain the oxidant/antioxidant balance, thereby improve the healing of wounds in diabetes. Vitamin E is a well-known antioxidant; its α-tocopherol isoform has scavenging effect on reactive oxygen species (ROS) and stabilizing effect on damaged cell membrane [25,26].…”
Section: Discussionmentioning
confidence: 99%